Pedro Arrupe and the Second Vatican Council - Madrigal, SJ, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Fr. Pedro Arrupe (1907-1991) was elected Superior General of Society of Jesus on May 1965. The renovation of the Church promoved by the Council Vatican II provoked a deep renewal inside the Society of Jesus. He was the man who hat to lead the Jesuits into a very turbulent period (1965-1983) in the history of the Church. He tried to adapt the mission and the ignatian Spirituality to the news times but being faithfull to the first intuitions of Saint Ignatius, in search of the essential. Arrupe directed the 31st and 32nd General Congregation and pushed the Society towards a deeper commitment with Justice and his new perspective (the defense of faith and promotion of justice) had an important influence on spirituality and mission.
Keywords: Arrupe; Society of Jesus; General Congregation 31; General Congregation 32; aggiornamento; mission; Vatican II; reception